Validation of Malay version short-form geriatric depression scale and study of prevalence of major depression and its associated psychcosocial factors among elderly inpatients at Universiti Sains Malaysia Hospital - Eow, Teh Ewe (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Background: Depression is pre valent among the elckrly physically ill inpatients and has important clini cal implications. but ol'ten under recogni zed and under treated. There is no previous Malaysian data on the preva lence of major depression among the elderly inpatients. Ohjcctivrs: This study aimed to validate the Ma1ay version of the short form Geriat ric Depression Scale (GDS) in order to determine the prevalence of major depression and its assoc iated psychosoc ial risk factors among the elderly inpatients hospitalized lor general medical condition. Methods: The st ucly consisted of 2 stages. First, the validation of the Malay version(! f)S: foll mvecl by a cross sec ti onal preva lence study. parti ci pated hy 271 elderly inpat ient s. Data we re co llected using a self-admini stered questionn aire, the va lidatecl M:d;1y vc rsion-CIDS and Wl IOQOI .-13REF. Ma_ior depression was de lin ed as score above the optimum cut-oiTpninl on Mal;1y version-( iDS determined at the vallidation study. Results: The validation study showed the itcn1-9 from Malay vcrsion-GDS-15 had no discrin1inatory value in diJTen.~ntiating cases and non-cases and poorly correlated with the total corrected itcn1 score. By on1itting the iten1-<>. the newly fortned scale, M-GDS-14. has satisf~tctory reliability and validity as a screening scale for depression an1ong physic~lly i1J elderly inpatients. At the cut ofT point of 7/R, the M-GDS-14 had 1 00°/o sensitivity and 92.0'% sp~cilicity in detecting major depression. The overall prevalence f(w n1a.inr d~prcssion was l7.lo/o. 25.9°/o for n1ale and 45.R0/o for fcn1alc. Under 1ntlltivariahle analysis. the len1ale to n1alc odds ratio for n1ajor depression was 2.2 (p == 0.03 ). Those depended on working as the primary source of personal incon1e, were at significant higher risk than pension group for m~jor depression (OR = 7.8). The sci f-rating of relatively having enough rnoncy to n1eet needs, satisfactory personal "I· relationship. adequate accessibility to inforn1ation needed and opportunity for leisure activities were all significant protective factors against nu~jor depression. Conclusion: The prevalence yielded in this study was relatively high. Clinician should he aware of this highly con1orbid condition along with patients' physical illness. Good social resources play in1portant role in preventing 1najor depression in the elderly inpatients.